The Right to the Sacrament of Anointing the Sick. The Issue of Children and Mentally Disabled - Trojanowski, Bartosz (Studia Warmińskie, 2021)
The spiritual goods of the Church, and especially the sacraments, are the right of all the faithful. Therefore, no one should unreasonably refuse them to the faithful. Particularly in the event of the danger of death, and more broadly also in sickness, the faithful should have access to the sacraments, including the sacrament of the Anointing of the Sick. However, in canon law, there are restrictions related to the possibility of receiving this sacrament. Among these limitations is the achievement of the use of reason, and thus, on the basis of general norms, it should be stated that children and equated to them suffering from mental diseases and intellectual disabilities were excluded. On the one hand, we have the right to the sacraments, including the Anointing of the Sick, which is for those who struggle with ailments, diseases, suffering which are heavy and can often lead to death. On the other hand, the Legislator himself imposes a restriction and requires the achievement of the use of reason. This in some way opens up the possibility of interpreting the intentions of the Legislator, since there is no obligation to reach the age at which reason is presumed to be used. Therefore, a theological and legal reflection was undertaken in order to verify the possibility of administering the sacrament to sick children and adults who have not achieved the use of reason, but have it to some extent. In this way, the Legislator’s intention was presented that everyone – to whom the sacrament of the Anointing of the Sick can really benefit spiritually, – could receive from this spiritual good of the Church.